2018
DOI: 10.31958/js.v9i1.606
|View full text |Cite
|
Sign up to set email alerts
|

ANALISIS KADAR LOGAM TIMBAL (Pb) PADA RAMBUT KARYAWAN SPBU

Abstract: Development in the field of health is the achievement of an optimal public health degree. Among people who are often exposed to air pollution such as lead metal (Pb) is a gas station officer. One of the objectives of this research is to figure out the differences of lead level (Pb) in the hair of SPBU workers who base on Jl. Ir. Juanda based on length of service period by using experimental research to analyze Pb metal at gas station workers. The population and sample of research is hair of three gas station w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Research in Padang explains that the longer you work, the greater the Pb metal content. The highest amount of Pb was found during the longest working period, namely 9-12 years with a metal content of Pb of 0.8175 mg/g (Mayaserli & Renowati, 2018). However, a statement from a study in Palu City explained that no matter how long the work period cannot fully determine the lead level in the body, no matter how long the work period is if the nutritional status and lifestyle are healthy can reduce the lead level in the body, and vice versa even if a person's working period is still in a new condition but if the pattern of life is not healthy it will affect the level of lead in the body, especially if someone smokes it will greatly affect the level of lead in a person's body, because cigarettes contain lead even if only a little.…”
Section: Working Periodmentioning
confidence: 96%
See 1 more Smart Citation
“…Research in Padang explains that the longer you work, the greater the Pb metal content. The highest amount of Pb was found during the longest working period, namely 9-12 years with a metal content of Pb of 0.8175 mg/g (Mayaserli & Renowati, 2018). However, a statement from a study in Palu City explained that no matter how long the work period cannot fully determine the lead level in the body, no matter how long the work period is if the nutritional status and lifestyle are healthy can reduce the lead level in the body, and vice versa even if a person's working period is still in a new condition but if the pattern of life is not healthy it will affect the level of lead in the body, especially if someone smokes it will greatly affect the level of lead in a person's body, because cigarettes contain lead even if only a little.…”
Section: Working Periodmentioning
confidence: 96%
“…Lead levels in the hair of gas station employees, the results of the study showed that length of work was a factor that influenced the amount of Pb metal content in hair. Lead levels in hair increased with length of service, the highest was found at 9-12 years of service, namely 0.8175 mg/g (Mayaserli, & Renowati, 2018). Lead that enters the worker's body comes from emissions from the work environment in the form of fumes around workers which become a hazard (Haider & Hashmi, 2014;Popović, Prokić-Cvetković, Burzić, Lukić, & Beljić, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Begitu juga dengan penelitian yang dilakukan pada rambut operator SPBU di Padang tahun 2018 menunjukkan adanya pengaruh masa kerja dengan tingginya kandungan logam Timbal di dalam tubuh, artinya semakin lama bekerja maka kandungan logam Timbal (Pb) juga akan semakin tinggi. Jumlah timbal teerbanyak ada pada kelompok masa kerja yang paling lama yaitu 9-12 tahun dengan kandungan Timbal sebesar 0,8175 mg/g Mayaserli et al (2018). Berdasarkan latar belakang diatas peneliti tertarik untuk melakukan penelitian tentang kandungan logam berat pada rambut petugas stasiun pengisian bahan bakar umum (SPBU) di Sidoarjo.…”
Section: Pendahuluanunclassified
“…Hair contains structural proteins, particularly keratin, which is composed of cysteine amino acids with disulfide bond groups (-S-S-) and cystine with sulfhydryl groups (-SH). Both of these groups enable hair to strongly bind to heavy metals like lead [10].…”
Section: Introductionmentioning
confidence: 99%
“…Whether in large or small amounts, lead in the body can be hazardous due to its toxic nature and accumulative properties within the human body [10]. Repeated or continuous exposure to lead, even in small quantities, can lead to the accumulation of lead in tissues and organs, ultimately causing lead poisoning [5].…”
Section: Introductionmentioning
confidence: 99%